Khorazmshah Atsiz and Rashididdin Vatvot (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2024)
The article covers events related to the relationship between Atsiz Khorezmshah and Rashiduddin Vatvot. The amazing events between them have been expressed to a certain extent in the book "Lubobu-l-Albab" by Muhammad Avfi. We filled in some information about Vatvot with the help of Davlatshah "Tazkirat-ush-shuaro".